Effect of Adsense on Deddy Corbuzier's YouTube on the Viewing Interests and Viewing Actions of Universitas Sumatera Utara Students - Alfi Syahri Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This article aims to analyze the effect of adsense on Deddy Corbuzier's Youtube on the viewing interests and viewing actions of Universitas Sumatera Utara (USU) Students. The theory used is the theory of mass communication, new media, uses and gratifications, interest and attitude theory. This type of research is quantitative with correlational methods. The total population in this study amounted to 16,874 people with a total sample of 400 respondents. The sampling technique uses rational sampling with the characteristics of students who have watched Deddy Corbuzier's Adsense Youtube. Data collection techniques are using questionnaires and library research. The results showed that adsense program ad impressions with viewing interest had a correlation value of 0.446, adsense program ad impressions with the act of watching had a correlation value of 0.579, and adsense program ad impressions with viewing interest with the act of watching had a correlation value of 0.633. Display of Adsense Program Ads on Deddy Corbuzier's Youtube Adsense influences Interest and Viewing Actions among USU Students. The results of the positive correlation value show a unidirectional relationship, that viewing interest will increase viewing actions on Dedy Corbuzier's YouTube adsense. The significance value is the existence of a significant relationship between the action variable and viewing interest.